Assessment of epithelial innate antimicrobial factors in sinus tissue from patients with and without chronic rhinosinusitis. Issue 11 (7th September 2014) - Lee, Jivianne T.; Escobar, Oswaldo H.; Anouseyan, Rabin; Janisiewicz, Agnieszka; Eivers, Edward; Blackwell, Keith E.; Keschner, David B.; Garg, Rohit; Porter, Edith
<x xml:space="preserve">Abstract</x> Background Airway secretions contain endogenous antimicrobial factors (AMFs) that contribute to the innate host defense of the respiratory tract. Antibacterial peptides as well as host‐derived lipids including cholesteryl esters have been detected in maxillary lavage fluid. Sterol O‐acyltransferase 1 (SOAT1) is a key enzyme in cholesteryl ester production. The purpose of this study is to determine if such intrinsic microbicidal molecules are acutely expressed within sinus tissue and to compare levels of expression between patients with and without chronic rhinosinusitis (CRS). Methods Sinus tissue was obtained from subjects with (24) and without (9) a history of CRS. Six CRS patients had nasal polyposis (CRSwNP). Immunofluorescence staining for human neutrophil peptide (HNP) was done as a marker for inflammation. Real‐time polymerase chain reaction (RT‐PCR) following RNA extraction was used to quantify the expression of SOAT‐1, the epithelial beta‐defensins (HBD2 and HBD3), and the cathelicidin LL37 with ribosomal protein, large, P0 (RPLP0) as the housekeeping gene. Results Immunofluorescence showed significant increase in HNP staining in CRS patients without nasal polyposis (CRSsNP) vs non‐CRS specimens (p = 0.010), in agreement with clinical inflammation status. SOAT1 messenger RNA (mRNA) expression was also upregulated in CRSsNP compared to non‐CRS (p = 0.041) and CRSwNP (p = 0.005) patients, whereas increases for HBD2 and HBD3 were less prominent. LL37 was either absent or expressed at very low levels in all samples. Conclusion Increased biosynthesis of SOAT1, a key enzyme for antimicrobial cholesteryl ester production, was observed in the sinus tissue of CRSsNP patients but not in CRSwNP patients. This further supports the novel concept of lipid‐mediated innate mucosal defense and delineates CRS with and without nasal polyposis as distinct subtypes.